Cartilha para orientação da pessoa idosa sobre o consumo de álcool - Lima, Jucélia Moraes de (2024)
Introduction: Life expectancy and the number of elderly people have increased exponentially, coupled with an increase in chronic non-communicable diseases related to lifestyle and the adoption of unhealthy habits, especially alcohol consumption.Objective: To build an educational health technology, like a booklet, to guide the elderly about alcohol consumption. Methods: This is a methodological study structured in four stages: 1st, an integrative review that aims to identify scientific evidence on the prevalence of alcohol consumption among the elderly and the risk and protective factors associated with this consumption, based on consultations in four databases from the last 10 years (2013 to 2023), using the terms "Aged; prevalence, alcoholism, binge drinking, risk factors"; 2nd and 3rd, documentary research: which aims to identify the elderly who use alcohol registered in primary health care, from the individual registration report of the e-SUS APS system, in the period from 2017 to 2023; and which aims to identify the seizures of alcoholic beverages carried out by the professionals of the Health Surveillance VISA, through the consultation of the seizure terms, in the period from 2013 to 2023, both referring to the municipality of Barra do Garças/MT; and the 4th from the construction of an educational technology applied to health to guide the elderly about the health risks of alcoholic beverage consumption.The data was analyzed descriptively. Results: The integrative review resulted in 1,938 articles, so six studies were part of the final sample, revealing a prevalence of alcohol consumption among the elderly ranging from 14% to 88.3%. Risk factors included being male, having a low level of education and not practicing physical activity. The protective factors were related to the fact that the elderly person had a chronic illness, had more schooling and was female. The documentary research found that 2,540 registered elderly people in primary health care in Barra do Garças/MT consumed alcoholic beverages, which corresponds to 13% of people who use this substance.The data also revealed a continuous increase in alcohol consumption among the elderly, which rose by 23%. In a survey of health surveillance records from 2013 to 2023, 1,738 alcoholic beverages were seized, the majority for reasons of expired shelf life (n=1,556). The booklet was created using the adobe illustration program and vectorized adobe photoshop images. It contains 14 illustrated pages in arial font, size 24, containing concepts about alcohol consumption in the elderly and measures aimed at reducing the harm caused by alcohol consumption in this population. Final considerations: the booklet developed as an educational technological product in health aims to inform, in a playful way, about alcohol consumption among the elderly and also offers three tips aimed at reducing the harm of alcohol consumption in this population, which makes this product possible for use in health education actions for the elderly population.